THE ROLE OF GUIDANCE AND COUNSELING TEACHERS TO OPTIMIZE SOCIAL CONSTRUCTIVISM IN LEARNING AT SCHOOL - Desta Alfia; Risma Nursyani; Ila Halimah; Kinanti Oktaviani; Alvin Nayandra Perangin Angin (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Social constructivism in learning is a form of educational theory that prioritizes increasing the logical and conceptual development of learners. What makes the problem is that students who construct their knowledge, not infrequently that the results of student construction do not match the results of the construction of scientists, causing misconceptions. This article is an analysis of the situation using qualitative methods. Qualitative methods are research whose preparation uses data collection techniques by conducting interviews and observations for collection. In addition, supporters are reading, recording, and reviewing data from journals and articles from electronic media and books related to